2019
DOI: 10.1108/jpbm-09-2017-1564
|View full text |Cite
|
Sign up to set email alerts
|

Role of consumer vanity and the mediating effect of brand consciousness in luxury consumption

Abstract: Purpose There has been substantial research on luxury globally, but there is a dearth of studies empirically investigating the key relationships affecting luxury consumption. The aim of this paper is to consider the role of consumer vanity and brand consciousness and to set their relationships in context of luxury consumption. Design/methodology/approach To measure consumer vanity, brand consciousness, attitude towards luxury brands and purchase intentions, pre-established scale items were adopted. Self-admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 82 publications
(121 reference statements)
6
32
1
1
Order By: Relevance
“…In marketing literature, research suggests that the behaviour of vanity is usually observed by consumers to signal their social status and wealth by consuming luxury brands [92,93]. As luxury brands are appearance-related conspicuous products, vanity plays a role in influencing, motivating, and promoting brands to the consumers [88,94].…”
Section: Vanity and Luxury Brand Valuementioning
confidence: 99%
“…In marketing literature, research suggests that the behaviour of vanity is usually observed by consumers to signal their social status and wealth by consuming luxury brands [92,93]. As luxury brands are appearance-related conspicuous products, vanity plays a role in influencing, motivating, and promoting brands to the consumers [88,94].…”
Section: Vanity and Luxury Brand Valuementioning
confidence: 99%
“…e quality of luxury products and the allure of designer brands are indispensable factors that should not be ignored when considering the online luxury consumption of consumers. Highend brands are perceived as premium quality [4]; hence, brand consciousness and attitude [6,7] and brand prominence [3] and uniqueness [5] figure largely as shopping motivators. Other scholars have investigated online luxury consumption from a cultural perspective, such as traditional Chinese attitudes toward face, social stability, and guanxi, together with political ideology [8], national norms, and global consumer culture [12].…”
Section: Online Luxury Consumptionmentioning
confidence: 99%
“…[6] Materialism, brand consciousness, consumer ethnocentrism, and bandwagon behavior Factors that affect Chinese consumers' attitude toward purchasing luxury foreign fashion goods online [20] Power deprivation Confirmed the effects of power deprivation on luxury consumption and provided practical suggestions for luxury brand managers and retail mall managers [3] Brand prominence and status consumption How the use of a prominent versus subtle branding strategy and status consumption affect consumers' intention to buy luxury products across emerging and mature markets [2] Consumer needs for uniqueness, self-monitoring of expressive behavior, and extrinsically motivated Examined the influence of consumer goal attainment (extrinsic and intrinsic) on the intention to purchase luxury products (explicitly versus subtly marked) [7] Consumer vanity, brand consciousness, and attitude Considered the role of consumer vanity and brand consciousness in the context of luxury purchases [5] Value orientations, such as self-enhancement values and openness to change; luxury values, such as social and uniqueness value Investigated the effect of four cultural value orientations on the values consumers ascribe to luxury products [21] Psychological and sociological factors like self-awareness, social comparison, and materialism Provided empirical evidence on the direct and indirect effects of the abovementioned psychological and sociological factors as the antecedents of bandwagon luxury consumption [22] Regulatory focus, goal orientation, and self-construal How consumers' promotion and prevention focus influence luxury purchase intentions Mobile Information Systems they will be much less likely to complete a purchase and less likely to refer to other customers because they are afraid to be deceived [30,31]. Some scholars have also proved that source credibility positively affects the purchase intention and word-of-mouth intention of consumers under divergent contexts [32][33][34][35].…”
Section: Source Credibility and Behavioral Intentionmentioning
confidence: 99%
See 2 more Smart Citations